Stability of limiting pressure behind soil gaps in contiguous pile walls in anisotropic clays. (April 2022) - Lai, Van Qui; Banyong, Rungkhun; Keawsawasvong, Suraparb
Highlights: A state of art approach to study limiting pressure behind soil gaps in contiguous pile walls. Advanced 2D finite element limit analysis for contiguous pile walls. Comprehensive design charts and tables are presented. A closed-form equation of the limiting pressure factor is presented. Abstract: New average FELA solutions for the problem of the limiting pressure behind soil gaps and the lateral force acting on a pile per unit length of a contiguous pile wall in anisotropic clay are investigated in this paper. The anisotropic undrained shear (AUS) model is utilized to determine anisotropic soil behaviour. The limiting pressure factor ( N ) is derived by varying dimensionless parameters such as the anisotropic ratio ( re ), the adhesion factor (α), and soil gap ratios ( S/D ) which are presented in the form of sample charts and tables. The failure patterns of the soil gaps are also conducted and explained in light of the impacting factors. A closed-form equation of the limiting pressure factor is presented in order to efficiently and precisely establish and evaluate an undrained limiting pressure behind soil gaps and the lateral force operating on a pile wall in practice.